2022
DOI: 10.1039/d2ma00038e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of joining temperature on the interconnection zone and electrical resistance of Ag/n-Mg2Si and Ag/n-Mg2Sn contacts

Abstract: 1. Study of the Ag contacted n-type Mg2X (X = Si, Sn) TE materials. 2. Successful correlation of the observed phases at the n-Mg2X/Ag interconnection zones with the thermodynamically favorable phases. 3. Calculation of the electrical contact resistances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Further research showed that this charge compensation mechanism is not strongly related to neither the newly grown reaction layer between the TE material and the electrodes nor the electrical sintering current that the samples are subjected to during the contacting procedure in the direct sinter press. [ 6b,c,10 ] Instead, it has been argued that the observed material degradation is majorly due to defect diffusion from the electrode to the TE material. Given the ubiquity of point defects and their crucial role in TE (and other) functional materials one might wonder why this problem has not appeared more prominently beforehand.…”
Section: Introductionmentioning
confidence: 99%
“…Further research showed that this charge compensation mechanism is not strongly related to neither the newly grown reaction layer between the TE material and the electrodes nor the electrical sintering current that the samples are subjected to during the contacting procedure in the direct sinter press. [ 6b,c,10 ] Instead, it has been argued that the observed material degradation is majorly due to defect diffusion from the electrode to the TE material. Given the ubiquity of point defects and their crucial role in TE (and other) functional materials one might wonder why this problem has not appeared more prominently beforehand.…”
Section: Introductionmentioning
confidence: 99%